2012
DOI: 10.1590/s0101-20612012005000021
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial properties of plant essential oils thymus vulgaris, cymbopogon citratus and laurus nobilis against five important foodborne pathogens

Abstract: In vitro antimicrobial properties of plant essential oils thymus vulgaris, cymbopogon citratus and laurus nobilis against five important foodborne pathogens Propriedades antibacterianas in vitro de óleos essenciais de thymus vulgaris, cymbopogon citratus e laurus nobilis contra cinco importantes bactérias patogênicas veiculadas por alimentosAlessandra Farias MILLEZI 1 *, Danila Soares CAIXETA 1 , Diogo Francisco ROSSONI 2 , Maria das Graças CARDOSO 3 , Roberta Hilsdorf PICCOLI 4 IntroductionThe essentials oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
(34 reference statements)
0
31
1
5
Order By: Relevance
“…The antibacterial activity of PIEO against L. monocytogenes, E. coli and S. aureus was previously determined through in vitro experiments (Desai et al, 2012;Millezi et al, 2012;. However, a literature review revealed that the activity of PIEO against L. monocytogenes, E. coli and S. aureus had not been investigated in fish fillet .…”
Section: Table1 Antimicrobial Activity Of Pulicaria Inuloides Andmentioning
confidence: 99%
“…The antibacterial activity of PIEO against L. monocytogenes, E. coli and S. aureus was previously determined through in vitro experiments (Desai et al, 2012;Millezi et al, 2012;. However, a literature review revealed that the activity of PIEO against L. monocytogenes, E. coli and S. aureus had not been investigated in fish fillet .…”
Section: Table1 Antimicrobial Activity Of Pulicaria Inuloides Andmentioning
confidence: 99%
“…These six basic lipophilic substances of the Laurus essential oil are able to penetrate through the cell membranes of microorganisms by means of polysaccharides, fatty acids, and phospholipids destruction which compose them. Antibacterial activity of the essential oil of Laurus is described in a lot of researches [39,40].…”
Section: фармация и фармакология т 5 № 3 2017mentioning
confidence: 99%
“…Эти шесть ос-новных липофильных веществ эфирного масла лавра в состоянии проникать через клеточные мембраны микроорганизмов, посредством разрушения полиса-харидов, жирных кислот и фосфолипидов, входящих в их состав. Антибактериальная активность эфирно-го масла лавра описана в многочисленных исследо-ваниях [39,40].…”
unclassified
“…El Thymus vulgaris, tal como se puede evidenciar en la Tabla 2, exhibe propiedades antibacterianas a concentraciones de 150, 175 y 200 mg/ml, en tal caso, Millezi et al (2012), reportaron la capacidad antimicrobiana que exhibía el Thymus vulgaris, en la cepa S. aureus (ATCC 25923), entre otras cepas en estudio,el mismo demostró que a partir de concentraciones de 5 mg/ml se observaba la presencia de un halo inhibitorio. Nadia y Rachid (2013) estudiaron el efecto del tomillo como antioxidante y antibacteriano para el control de bacterias patógenas como E. coli y S. aureus (ATCC 25923), este último reporto la presencia de halo inhibitorio superior a 15 mm.…”
Section: │ 49unclassified
“…Sin embargo, la formación del halo reportado por este investigador es superior a los 4 mm. Así mismo, Millezi (2012) y Ghadiri (2014), reportaron la actividad antimicrobiana que tenía Laurus nobilis.…”
Section: Introductionunclassified